Unrevealed caries in unerupted teeth: A prevalence study - Sapna Konde; C S Sri Darshini; Manisha Agarwal; Preetha Peethambar (Wolters Kluwer Medknow Publications, 2018)
Background: Preeruptive caries are an abnormal, well-circumscribed, radiolucent area, occurring within the coronal dentinal tissue close to the dentinoenamel junction of unerupted teeth. OPGs are commonly taken in children for assessing the dental age and eruption sequence. It can be used as a good diagnostic source for detection of PEIR defects. Aim: The aim of this study is to determine the prevalence of Preeruptive intracoronal dentin radiolucencies in unerupted permanent teeth from orthopantomogram. Settings and Design: A total of 1000 standard orthopantomographs of children below 12 years of age were collected and examined. Methodology: The OPGs were examined for PIER defects in the unerupted teeth. The prevalence of PEIR defects was assessed with respect to age, sex, tooth, and the arch involved. Statistical Analysis: The data obtained were tabulated and analyzed. The prevalence was calculated in percentage. Results: The participant prevalence was 13.6%. The teeth prevalence was 1.20%. The majority (38.9%) of defects were seen in the in the mandibular first premolar. Almost half of the lesions were located on the mesial side (52.3%), with a size less than one-third of dentine thickness (53%). Conclusion: PIER defects constitutes an important part of anomalies associated with unerupted teeth and thus needs a proper understanding of its prevalence, etiology, manifestations, and complications. These defects are usually overlooked by clinicians while interpreting radiographs; however, it is of utmost importance to promptly diagnose these defects thus preventing further complications.